A case of eruptive xanthomas with thousands of lesions. - Wang, S.; Xu, B.; Zhang, R. (European Journal of Pediatric Dermatology, 2022)
A 27-year-old man with obesity had a 3-month history of progressive thousands skin lesions on the extensor surfaces of his extremities and trunk. Dermatoscopy showed a pale yellow irregular and unstructured substance, with arboriform telangiectasias. Histological examination revealed foamy cells and a few multi-nucleate giant cells in the dermis. Based on the information mentioned above and the results of blood tests, the patient was diagnosed as eruptive xanthoma and hyperlipidemia.